Epithelial‐Mesenchymal Plasticity in the D‐Meso‐Sonobe Mesothelioma Cell Line: A Putative Model of Epithelial–Mesenchymal Transition in Mesothelioma - Hiroshi Okubo; Yuki Hanamatsu; Chiemi Saigo; Sonobe Hiroshi; Tamotsu Takeuchi (Thoracic Cancer)
ABSTRACT Epithelial‐mesenchymal transition (EMT) plays a crucial role in carcinogenesis, including mesothelioma. D‐Meso‐Sonobe is a deciduoid‐type mesothelioma cell line with morphological features similar to those of epithelioid cells. Here, we report that D‐Meso‐Sonobe cells exhibit spindle cell mesenchymal features under continuous confluent culture conditions. The spindle cell mesenchymal D‐Meso‐Sonobe expresses zinc finger E‐box‐binding homeobox 1 (Zeb1), which is a master regulator of EMT in the nucleus. Xenoplanted D‐Meso‐Sonobe cells expressed nuclear Zeb1 and yes‐associated protein at the cancer invasion front and focally expressed integrin subunit alpha V and actin alpha 2, which are molecular phenotypes acquired by EMT in mesothelioma. Subsequent RNA sequencing revealed that lysyl oxidase like 1 (LOXL1) was more highly expressed in cultured spindle mesenchymal D‐Meso‐Sonobe cells than in epithelioid cells. LOXL1 immunoreactivity was observed at the invasive front of xenoplanted D‐Meso‐Sonobe cells. The epithelial‐mesenchymal plasticity of D‐Meso‐Sonobe cells may be applicable for the development of candidate molecular agents targeting EMT in mesothelioma.